Proceedings of the 8th Australasian Conference on Interactive Entertainment: Playing the System 2012
DOI: 10.1145/2336727.2336741
|View full text |Cite
|
Sign up to set email alerts
|

Experiences with design patterns for oldschool action games

Abstract: This article discusses the application of an Alexandrian pattern language to the design of interactive systems. It grew out of an University course titled A Pattern Approach to Action Game Design, which was offered as an elective in the Creative Technologies program at Auckland University of Technology, New Zealand, in 2011. We sketch out the idea of design patterns and describe our experiences with the process of using them for designing oldschool action games, that is, finding patterns, making a language, us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
(2 reference statements)
0
2
0
Order By: Relevance
“…Björk and Holopainen later applied the ideas of design pattern to game design, listing hundreds of generic game design patterns in an influential book [9,10]. Several authors have further identified a number of game design patterns in specific game genres [11,12,13,14].…”
Section: B Design Patternsmentioning
confidence: 99%
“…Björk and Holopainen later applied the ideas of design pattern to game design, listing hundreds of generic game design patterns in an influential book [9,10]. Several authors have further identified a number of game design patterns in specific game genres [11,12,13,14].…”
Section: B Design Patternsmentioning
confidence: 99%
“…In the context of games have Björk and Holopainen suggested an extensive collection of patterns for game design [8]. Similarly, others have looked into game mechanics [9] and specific game contexts like FPSs [10], RPGs [11], and action games [12]. There have also been some attempts to formulate abstract level design patterns that can be specialised to concrete metrics for different level types [13].…”
Section: Introductionmentioning
confidence: 99%